Death scene - Perry, Carol J. (Perry, Carol J. Witch City mystery., 2024)
"Between documenting the progress of the movie, corralling starstruck autograph seekers and fans, and managing unmanageable traffic on Salem's narrow streets, Lee and her police detective husband, Pete Mondello, are beyond busy. Even Lee's best friend, River North, tarot card reader and practicing witch, gets in on the action, landing a job as a stand-in and body double. But it only takes one interview for Lee to realize that the male and female leads--whose roles include torrid love scenes--despise each other. Yet the problem is short-lived, literally... When the gorgeous lead actress is found dead on a set staged to replicate the room where suspected witches were tried in 1692--and her on-screen lover, in full costume, is discovered sound asleep in her trailer--the hunt is on for a killer on the loose. Nevertheless, the producer decrees "the show must go on!" Now, even with help from River, Lee's Aunt Ibby, and O'Ryan, a remarkably clairvoyant gentleman cat, sorting out a witch's brew of secrets, sorcery, and special effects might turn Lee's documentary into her own final act..."--